Are in-market control systems for sunscreens adequate for consumer protection? A review of the legal framework regulating sun protection factor labels in Europe - Aleix Bacardit (BMJ Publishing Group, 2023)
Public health authorities and regulations in Europe protect the population against the damaging effects of excessive solar ultraviolet radiation through, among other means, monitoring marketed sunscreens and enforcing compliance with sun protection factor labelling requirements. In-market control processes are fundamental and complementary to other public health initiatives in a context of suboptimal sunscreen use in real-world settings. However, the laboratory testing method used for determining the sun protection factor of sunscreens is known to produce variability of results. The combination of an inherently variable testing method with the necessary rigidity of regulations generates volatility in the decision-making process followed by regulators during official in-market controls and exposes sunscreens to be susceptible to accidental mislabelling challenges. This leads to a paradoxical situation that may leave most sunscreens incorrectly labelled in the market and to a potential dilemma for authorities. The issue may get further amplified when non-official sources echo and broadcast uncontrolled messages about sunscreens to the public. Amending current regulation with a tolerance level to compare results that accommodates the variability of results from sun protection factor tests would ease decision-making, bring robustness to an uncertain legal landscape, make more efficient the efforts to convey consistent public health messages about the benefits of sunscreen use and better protect users. There are precedents of using tolerance levels for regulatory decision-making in other fields, and a review of the applicable legal landscape in Europe reveals that implementing it for sunscreens would only require one change to current cosmetics law.